German Instrumental Music of the Late Middle Ages: Players, Patrons, and Performance Practice - Polk, Keith (Cambridge [England] New York Cambridge University Press, 1992)
This book describes instrumental music and its context in German society of the late middle ages - from about 1350 to 1520. Players at that time improvised, much like jazz musicians of our day, but because they did not use notated music, only scant remnants of their activity have survived in written sources, and much has been left obscure. This book attempts to reconstruct an image of their music, discussing the instruments, ensembles, and performance practices of the time. What emerges from this study is a fundamental reappraisal of late medieval culture. A musical life is reconstructed which was not only extraordinary in its own time, but which also laid the foundations of an artistic culture that later produced such giants as Schütz, Bach, Mozart and Beethoven.
Includes bibliographical references (p. 252-266) and index.
Keywords: Middle Ages (500-1400); 15th Century (1401-1500); 16th Century (1501-1600); Instrumental music; Instrumentation; Performance; Patronage; Musical interpretation; Music history; Nobility; Institution; Germany